Assessment of Pentraxin 3 and Some Biomarker in Patients with Nonalcoholic Fatty Liver Diseases - Salam Abass , Mariam; Ghanim , Ghosoon; Abdul–Hussein Al-Hilly , Ahmed (Hammurabi Journal of Medical Sciences, 2024)
Background: Globally, one of the most frequent causes of chronic liver disease is non-alcoholic fatty liver disease (NAFLD). About 30% of the general population suffers from nonalcoholic fatty liver disease (NAFLD), a highly widespread condition. In some populations, however, such as those with type 2 diabetes mellitus (T2DM) and obesity, the prevalence is significantly higher, reaching 60% and 90%, respectively. Objective: this research was to assess the concentrations of particular biomarkers, such as pentraxin 3, and liver enzyme, in serum from individuals with and without fatty liver disease, nonalcoholic steatohepatitis, and nonalcoholic fatty liver disease (NAFLD). Material and Method: In this investigation, 90 participants in total were divided into three groups: 30 patients with NAFLD, 30 patients with NASH, and 30 people in the control group. The severity of the condition was evaluated by analyzing biomarker levels, such as pentraxin 3 and liver enzyme. Microsoft Excel 2019 and SPSS software were used to assess the data gathered between November 2023 and April 2024. Result: Serum PTX3 level was increased in the NAFLD group and NASH compared to the control but increased particularly in NAFLD patients. Conclusion: serum PTX3 level is a useful tool to assess and diagnose fatty liver diseases.